2020
DOI: 10.5798/dicletip.705814
|View full text |Cite
|
Sign up to set email alerts
|

New Uses of Platelet-Lymphocyte Ratio for Bleeding Risk Stratification in Patients with Nonvalvular Atrial Fibrillation: A Pilot Study

Abstract: Objective: The primary aim of this study was to investigate the role of platelet-lymphocyte ratio (PLR) to predict bleeding risk in nonvalvular atrial fibrillation (NVAF). Secondary aim was to determine the possible relation between PLR and thromboembolic and bleeding risk scores. Tertiary aim was to evaluate the predictive value of PLR for the patients in the therapeutic international normalized ratio (INR) range. Method: PLR was calculated from the complete blood count of 228 patients who were under warfarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that the increase in PLR is associated with venous thrombosis 26 . Whereas PLR has been reported to be a potentially useful parameter to detect the risk of bleeding 27 . Acer et all., reported that PLR decreased significantly after treatment with Omalizumab in patients with CSU 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the increase in PLR is associated with venous thrombosis 26 . Whereas PLR has been reported to be a potentially useful parameter to detect the risk of bleeding 27 . Acer et all., reported that PLR decreased significantly after treatment with Omalizumab in patients with CSU 22 .…”
Section: Discussionmentioning
confidence: 99%